1999
DOI: 10.1055/s-2007-971154
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Venous Bubbles in Recreational Diving: Relationships with Age, Weight, Maximal Oxygen Uptake and Body Fat Percentage

Abstract: Decompression sickness (DCS) is recognized as a multifactorial phenomenon depending on several individual factors, such as age, adiposity, and level of fitness. The detection of circulating venous bubbles is considered as a useful index for the safety of a decompression, because of the relationship between bubbles and DCS probability. The aim of this work was to study the effects of individual variables which can be assessed non invasively, on the grades of bubbles detected 60 min, after diving by means of Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 0 publications
1
18
1
3
Order By: Relevance
“…[84][85][86] The benefit of physical conditioning was also suggested by the association of low VGE incidence with divers in whom maximal oxygen consumption was high. 87 In summary, the effect of exercise before decompression appears to depend on the intensity of exercise, the interval between exercise and decompression, and physical conditioning. Studies of anaerobic exercise before altitude exposure in humans and animals found evidence of increased DCS risk if the exercise took place immediately or within several hours of decompression but that the risk was not increased after a 1-day interval.…”
Section: Exercise Before Pressure Exposure: Bubble Nucleationmentioning
confidence: 99%
“…[84][85][86] The benefit of physical conditioning was also suggested by the association of low VGE incidence with divers in whom maximal oxygen consumption was high. 87 In summary, the effect of exercise before decompression appears to depend on the intensity of exercise, the interval between exercise and decompression, and physical conditioning. Studies of anaerobic exercise before altitude exposure in humans and animals found evidence of increased DCS risk if the exercise took place immediately or within several hours of decompression but that the risk was not increased after a 1-day interval.…”
Section: Exercise Before Pressure Exposure: Bubble Nucleationmentioning
confidence: 99%
“…There was a bigger variation in dive experience and we expect these divers in average to be less experienced, although we can not confirm this. These data also contained a wide varity of other individual parameters like age, fat percentage and fitness level, that are known to influence the Doppler results [4]. Additionally these exposures are predominately multi-day diving, which in the Croatia study were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Mit Einführung der Doppler-Diagnostik gelang es, Inertgasblasen nach Tauchgängen zu detektieren, und inzwischen wurden solche Blasen auch bei asymptomatischen Probanden vielfach nachgewiesen [8,9,11,14]. Die Gefahr pathologischer Effekte dieser Inertgasblasen ist abhängig von deren Menge und Lokalisation.…”
Section: Physiologische Kardiovaskuläre Effekte Des Tauchensunclassified
“…Darüber hinaus konnte Doppler-sonographisch gezeigt werden, dass es bei übergewichtigen Tauchern während bzw. unmittelbar nach der Dekompression zu einer vermehrten Gasblasenbildung kommt [8,9]. Erklärend sei hier erwähnt, dass prinziTabelle 2.…”
Section: Hyperlipidämie Und Adipositasunclassified